Psychosocial Problems Among School Adolescents in Rupandehi - Bhandari, Sharmila; Acharya, Sabitri; Lamichhane, Kavita; Gaire, Hari (Journal of Universal College of Medical Sciences, 2022)
INTRODUCTION Adolescence is a crucial period for developing and demanding signiﬁcant adjustment to the physical and psychological changes. Because of these changes occurring in their body during this developmental stage, they are more vulnerable to develop psychosocial problems. The main objective of this study is to assess the prevalence of psychosocial problems among school adolescents. MATERIAL AND METHODS A cross sectional study was conducted to assess psychosocial problems among 217 school going adolescents in Rupandehi by using non-probability purposive sampling technique. Self-administered questionnaire was used to collect the data and collected data were analyzed by using descriptive and inferential statistics with Statistical Package for Social (SPSS) Software Version 20. RESULTS The ﬁndings of the study revealed that 33.6% of the respondents had psychosocial problems. There was statistically signiﬁcant association between both parents involvement in occupation, family income and family problems with psychosocial problems. CONCLUSION Based on the study ﬁndings, it is concluded that one third of the adolescents had psychosocial problems. Family factors were involved for the problems. Early identiﬁcation and adequate counseling might help to prevent adverse consequences. So, family, school and health care provider combined effort plays an important role.